At the end of the road - Guerrero San Martín, Fabiola (2020)
Talking about the proximity of death is questioning, for many a taboo or topic to avoid. However, it is not far from our present reality and invites us to reflect on it. A great American author, who died at the age of eighty-seven, left us with a memorable phrase: "Death is the last journey, the longest and the best." (Tom Wolfe), in the accurate reflection of who starts not to return. Many are the factors that have influenced to assume this reality, from the recurrence of the news, the natural fear of death, the fragility in the face of illness, the seeing of those close to oneself, old age and childhood; own personal and family experience, fear, fear, loneliness and sadness together with a host of emotions that are necessary to assume and control. The handling of mourning and mourning is not far from this reality, as well as the consequent coping with the death of those who are close and even close to their own departure. Bioethics also invites us to reflect on palliative care, respect for human dignity and value, also proposing support aids for human well-being.